Projects-Based Mid-Assessment Model of English at the Junior High School Grade 7 - Vinindita Citrayasa (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2015)
This article offers a project-based model of mid-term assessment for junior high school grade seven. The model was proposed to help English teachers in assessing their students‟ learning process and learning results according to Curriculum 2013. English teachers still find difficulty creating an authentic and holistic assessment due to the time limitation. The research questions are first, whatthe model of project-based mid-term assessment of English at the junior high school grade 7 look likes and second, how the project-based mid-term assessment support teachers to conduct mid-term assessment.Thisis R D research, which has two goals: the research goal and project goal. First, the research goal is to present the iconic model version of authentic mid-term assessment of English learning. The project goal is to develop the authentic mid-term assessment of English learning for junior high school students and to understand the teachers‟ perceptions of this assessment. The results of the pilot study showed that this model was authentic and holistic. However the proposed model still needs revisions in order to become more effective in assessing students‟ learning process.